Zn 2+ ‐Driven Self‐Amplifying Nanoplatform Enables Cascade Photothermal–Gene Therapy via Mitochondrial Disruption - Zhi Li; Yuhong Chen; Youfei Zhang; Luzhen Huai; Xingzhou Zhu; Xue Mo; Jiahao Wang; Kui Zeng; Jie Wang (VIEW, 2026)
ABSTRACT The therapeutic efficacy of photothermal–gene combination strategies is often limited by intrinsic cellular stress resistance and insufficient intracellular amplification. Here, we report a Zn 2+ ‐activated nanoplatform (DN/Au@ZIF‐8) that enables a self‐amplifying therapeutic cascade through mitochondrial disruption. Upon exposure to the acidic tumor microenvironment, the ZIF‐8 framework undergoes rapid degradation, releasing Zn 2+ ions, gold nanorods, and a structure‐switchable DNA nanocomplex. The liberated Zn 2+ disrupts mitochondrial function, leading to ATP depletion and elevated reactive oxygen species, which collectively sensitize tumor cells to photothermal stress. Concurrently, the pH‐responsive I‐motif DNA undergoes conformational transformation to trigger efficient intracellular siRNA release and C‐myc silencing, further weakening cellular stress tolerance. These processes establish a self‐reinforcing loop in which mitochondrial dysfunction amplifies photothermal damage, while gene silencing suppresses adaptive resistance. As a result, DN/Au@ZIF‐8 achieves markedly enhanced tumor ablation both in vitro and in vivo. This work highlights a metal ion‐driven strategy to reprogram intracellular stress responses and provides a conceptual framework for designing cascade‐amplified nanotherapeutics.